EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, DAN SATISFACTION) TERHADAP PEMBELAJARAN MATEMATIKA SISWA KELAS VII SMP YP PGRI 4 MAKASSAR - Andi Tenriawaru, Ika, Jeranah (STKIP Paris Barantai, 2023)
This research aims to determine the effectiveness of ARIAS learning model on mathematics learning for class VII students of SMP YP PGRI 4 Makassar. The type of this research is pre-experimental with one-group pretest-posttest design. The population of this research is the seventh grade students of SMP YP PGRI 4 Makassar. The sample was 7 males and 18 females chosen by saturated sampling technique. Statistical analysis used is descriptive and inferential analysis. Based on descriptive analysis: (1) Mathematics learning outcomes of students in pretest obtained an average of 58.24 standard deviations of 16.048 with completeness of 28%, while learning outcomes in posttest were in good category with an average of 76.96 standard deviations of 9.016 with classical completeness of 92% , while the average N-gain is 0.45 in the medium category; (2) the implementation of learning obtained a percentage of 92.19 with a very good category; (3) student activity obtained an overall percentage of 81.82% in good category; and (4) student responses were obtained in a positive category with a score of 88%.